PEMIKIRAN DAN AKTIVISME DAKWAH BEDIUZZAMAN SAID NURSI (1877-1960) - Ichwansyah Tampubolon (Program Studi Pengembangan Masyarakat Islam, 2018)
AbstractBediuzzaman Said Nursi’s thoughts and activities on da’wah had been an unique model of the responses to western modernization in Turkey after the declining Ottoman Empire in nineteenth and early-twentieth centuries. Nursi intended to provide an Islamic answer based on Qoranic values to the attacks of westernization and secularization by several strategies of da‘wah with using cultural and political approach. He also had used special methods which can be summarized with three phrases: mânevi jihad (jihad of the word), publicated writings, and positive action. His thoughts and activities on da‘wah had impacted strongly on rising The Nur Community (Nurculuk) as the most significant religious and social movement with millions of adherents and a strong institusional system throughout the country. The Nur Community had published largely Nursi‘s thoughts round of the world and paid attention to realize his Risale-i Nur’s doctrines in serving of all human being in their daily life in the modern era.